Image of Iraqis in The Cinema of Sacred Defense - Abdollah Givian; Zohreh Tavakoli (Taḥqīqāt-i Farhangī-i Īrān)
Regarding representational function of media, the current dissertation intends to examine the changes in the representation of the image of the Iraqis in the Sacred Defense Cinema. Iraqies have been pictured as the "Others" during last three decades. Due to the importance and role of sacred defense and its cinematic representations of "Self" and "Other" and thereby its contribution in the process of reconstruction of Iranian national identity this research is aimed at studying represented images of Iraqies and its changes during last three decades. To reach this objective I first examined the concept and theories of representation as stated by Richard Dyer and Stuart Hall. Then to complement Hall’s theories I referred to other thinkers in the field of identity theory, ‘self’ and ‘the other’ as stated. In the chapter on methodology I’ve benefited from a combination of the patterns presented by Kate Selbi, Ran Kallory and Rolan Bart to analyze the texts.The findings of this thesis demonstrates that in order to depict the Iraqis in the sixties verbal codes were primarily used whereas in the seventies and the eighties social and technical codes were most used respectively.In the first decade Iraqis were portrayed as those people who are imagined to be cruel, inhuman, in which the emphasis was laid on the impact of the Iraqi’s invasion. In the second decade we see Iraqi’s depicted as dumb and fat people having thick moustaches and rough voices and in the third we see this portrayal to be transformed where Iraqi’s are shown to be our Muslim brothers who have been forced to fight in the war. Having observed, examined and analyzed the films, we found out that when facing ‘the other’, i.e. the Iraqis, the metaphor of the boundary or border was used. This border is seen between ‘self’ and ‘the other’, i.e. the Iranians and the Iraqis in all the chosen movies on the Sacred Defense. In the first decade there was an objective and real boundary whereas in the second we saw a transformation stage, where boundaries between ‘self’ and ‘the other’ were loose and shaking and finally over the third decade borders got utterly symbolic.